2020
DOI: 10.18805/lr-4208
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability, Diversity and Trait Correlation Analysis in Common Bean (Phaseolus vulgaris L.) Genotypes

Abstract: The present investigation was undertaken to study the genetic variability, diversity through cluster analysis and correlation among yield attributing traits. The experimental material is comprised of 63 diverse germplasm accessions including three check varieties were evaluated in augmented design during Rabi 2015-16 at IIPR, Kanpur. In this study, totally nine traits, namely, days to fifty per cent flowering (DF), days to maturity (DM), plant height (PH), number of branches per plant (NBP), number of pods per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
5
9
0
Order By: Relevance
“…The genetic parameters of traits that exhibited genetic variability in the material evaluated showed heritability above 80%, which indicates a greater association between phenotypic and genotypic values, while the highest estimates of GCV were observed in PH, POP, Y and SM, followed by SPO and BP, which indicates greater genetic variability and the possibility of genetic gain in these traits. Similar results were observed by Basavaraja et al (2021) who reported high GCV for PH, POP, Y and SM followed by BP and SPO, and high h 2 for PH, DM, DF, SM, Y, POP and SPO. Positive and significant genotypic correlations were observed between the PH trait with DA, DM, POP and SPO.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The genetic parameters of traits that exhibited genetic variability in the material evaluated showed heritability above 80%, which indicates a greater association between phenotypic and genotypic values, while the highest estimates of GCV were observed in PH, POP, Y and SM, followed by SPO and BP, which indicates greater genetic variability and the possibility of genetic gain in these traits. Similar results were observed by Basavaraja et al (2021) who reported high GCV for PH, POP, Y and SM followed by BP and SPO, and high h 2 for PH, DM, DF, SM, Y, POP and SPO. Positive and significant genotypic correlations were observed between the PH trait with DA, DM, POP and SPO.…”
Section: Resultssupporting
confidence: 88%
“…In this work, it was used to identify clusters of traits correlated with each other and with yield, allowing to discard those that are redundant and to increase the selection efficiency in the common bean breeding program. Similar studies carried out and published in Mozambique are scarce, however, several studies in the world, such as Ejara et al (2017), Oliveira et al (2018), AlBallat and Al-Araby (2019), Sharma et al (2019), Medianeira Giroletta dos Santos et al(2020, Yohannes et al (2020) and Basavaraja et al (2021) showed the importance identifying traits of interest that improve the yield of common bean. Studying the variability and relationships between traits is one of the most important steps in the initial genetic improvement program aimed at developing highyielding varieties.…”
Section: Introductionmentioning
confidence: 87%
“…Our results were in agreement with the results of Muniswamy et al (2014), Chaudhary et al (2016) and Shruthi et al (2020). Several researchers' viz., Mohan et al (2021), Remzeena et al (2021 and Basavaraja et al (2021) in other legume crops also gave emphasis on need of high genetic diversity to create the high genetic variation and their results were in conformity with our findings.…”
Section: Cluster Means For Different Characterssupporting
confidence: 93%
“…Percentage increase over check Variety Ooty 1 is 14.59 for green pod yield by its superior performance across the environments over the check variety (Table 7). Such high yield in french beans was also obtained by Reddy et al (2021), Sheik et al (2020, Basavaraja et al (2019), Kargiotidou et al (2019) and Pratap et al (2021).…”
Section: Methodssupporting
confidence: 56%